Anhydride Grafting on Carbon Nanotubes Using Ultrasound and its Effect on Polypropylene Nanocomposite Properties. Issue 10 (3rd July 2021) - Martinez Colunga, Juan Guillermo; Sanchez-Valdes, S.; Ramos de Valle, L.F.; Ramirez-Vargas, E.; Benavides Cantú, R.; Perez Camacho, O.; Avila-Orta, C. A.; Espinoza-Martínez, A. B.; Mata-Padilla, J.M.; Cruz Delgado, V. J.; Lozano, Tomas
ABSTRACT: Polypropylene composites and multi-walled carbon nanotubes (MWCNTs) modified with maleic anhydride (MA) and itaconic anhydride (IA) were prepared and their effect on the performance of nanocomposite properties was studied. Modification of the MWCNT was carried out in the presence of ultrasound varying the molar ratio of anhydride and dicumyl peroxide (BPO). PP nanocomposite with anhydride grafted MWCNT showed an increase, higher than 15%, in tensile strength and elastic modulus and a displacement of crystallization temperature (Tc) to higher temperatures, 1.5°C and loss weight temperature to higher temperatures, 30°C. This behavior was attributed to the better anhydride grafting in the MWCNTs induced by ultrasound.